2017
DOI: 10.1016/j.fcr.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Do no-till and pig slurry application improve barley yield and water and nitrogen use efficiencies in rainfed Mediterranean conditions?

Abstract: Tillage and N fertilization strategies including mineral and organic sources need to be studied in combination given their importance on the production cost that farmers face and their potential interaction on crop performance. A four-year (2010-2014) experiment based on barley monocropping was carried out in NE Spain in a typical rainfed Mediterranean area. Two tillage treatments (CT, conventional tillage; NT, notillage) and three rates of N fertilization (0; 75 kg N ha-1 , applied at top-dressing; 150 kg N h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
4
15
0
1
Order By: Relevance
“…These results are in line with earlier studies reporting the high potential of NT to enhance crop yield in non-irrigated field management [31]. The efficacy of cowpea to grow under water deficient conditions and with reduced or no tillage was also documented by Moroke et al [32] in the experimental area of Texas, and by Ahamefule and Peter [33] in Nigeria.…”
Section: Suitability Of V Unguiculata For Mediterranean Casupporting
confidence: 90%
“…These results are in line with earlier studies reporting the high potential of NT to enhance crop yield in non-irrigated field management [31]. The efficacy of cowpea to grow under water deficient conditions and with reduced or no tillage was also documented by Moroke et al [32] in the experimental area of Texas, and by Ahamefule and Peter [33] in Nigeria.…”
Section: Suitability Of V Unguiculata For Mediterranean Casupporting
confidence: 90%
“…Considering the return period of the precipitation, there is a probability between 60-70% of drainage from 6.1-7.2 mm of water during the winter season, the most prone to leach NO 3 − -N to the groundwater. The results alert about drainage in dryland agriculture systems and the potential associated impacts, contrary to the premised by other authors [48]. This scenario reinforces the importance of our results for environmental impacts over underground waters by solutes than can be leached.…”
Section: Drainage Modellingsupporting
confidence: 83%
“…These differences were clearly evident in dry years. Plaza-Bonilla et al (2017) found out that for a given N rate (0; 75 kg N/ha; 150 kg N/ha), the use of organic fertilisation significantly increased the water use efficiency in both tillage methods (conventional tillage and no-tillage). Hlisnikovský and Kunzová (2014) reported the results from the long-term field experiment.…”
Section: Resultsmentioning
confidence: 99%